What sort of sorcery is this?

Algebra Level 2

{ a b = a b a b = a 3 b \large{ \begin{cases} ab = a^b \\\\ \frac{a}{b} = a ^ {3b} \\ \end{cases}}

a a and b b are real numbers such that a > 1 a > 1 and b 0 b \neq 0 , satisfying the above system.

Find b a . b ^ { -a}.


The answer is 16.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

7 solutions

Sharky Kesa
Jul 2, 2015

Since a b = a b ab = a^b and a b = a 3 b \dfrac {a}{b} = a^{3b} , we have

a 2 = a b × a b = a b × a 3 b = a 4 b . a^2 = ab \times \dfrac {a}{b} = a^b \times a^{3b} = a^{4b}.

Therefore, b = 1 2 b = \dfrac{1}{2} .

Substituting, we obtain 1 2 a = a 1 / 2 \dfrac{1}{2}a = a^{1/2} so a 1 / 2 = 2 a^{1/2} = 2 and a = 4 a=4 .

Then b a = ( 1 2 ) 4 = 16 b^{-a} = \left (\dfrac{1}{2} \right )^{-4} = \boxed{16} .

Moderator note:

You missed explicitly stating that "Hence b = 1 2 b = \frac{1}{2} ".

Great question about exponents!

Could you please explain why a^b and a^3b are equal to a^2?

Im having a hard time understanding the logic behind it

Andrey Trudolubov - 5 years, 11 months ago

Log in to reply

Since a b × a b = a 2 b b = a 2 \dfrac {a}{b} \times ab = \dfrac {a^2 b}{b} = a^2 . Now, we know that a b = a 3 b \dfrac {a}{b} = a^{3b} and a b = a b ab = a^b , we have that a b × a 3 b = a 2 a^b \times a^{3b} = a^2 . This, in turn, gives us a 3 b + b = a 2 a^{3b+b} = a^2 which boils down to a 4 b = a 2 a^{4b} = a^2 .

Sharky Kesa - 5 years, 11 months ago

Log in to reply

i am ok in maths but i need to know how a*a/b = a^b * a^3b ?

why do we say they will be equal if we multiply them?

Raja Raman - 5 years, 11 months ago

he multiplied the tow equations ab*a/b

Hesham Dakrory - 5 years, 11 months ago
Daniel Turizo
Jul 9, 2015

By the first equation we get:

b = a b 1 ( 1 ) b = a^{b - 1} \qquad (1)

By the second equation we get:

1 b = a 3 b 1 \frac{1}{b} = a^{3b - 1} b = a 1 3 b ( 2 ) b = a^{1 - 3b} \qquad (2)

As (1) = (2) then:

a b 1 = a 1 3 b a^{b - 1} = a^{1 - 3b} b 1 = 1 3 b b - 1 = 1 - 3b b = 1 2 ( 3 ) b = \frac{1}{2} \qquad (3)

Replacing (3) in (1):

1 2 = a 1 2 = 4 \frac{1}{2} = a^{ - \frac{1}{2}} = 4

Therefore:

b a = ( 1 2 ) 4 = 16 b^{ - a} = \left( {\frac{1}{2}} \right)^{ - 4} = 16

Chew-Seong Cheong
Jul 10, 2015

a b = a 3 b = ( a b ) 3 = ( a b ) 3 = a 3 b 3 b 4 = a 2 b = a 1 2 a b = a ˙ a 1 2 = a 1 2 = a b b = 1 2 a b = a 2 = a 1 2 a 1 2 = 2 a = 4 b a = ( 1 2 ) 4 = 16 \begin{aligned} \frac{a}{b} & = a^{3b} = (a^b)^3 = (ab)^3 = a^3b^3 \quad \Rightarrow b^4 & = a^{-2} \quad \Rightarrow b = a^{-\frac{1}{2}} \\ \Rightarrow ab & = a\dot{} a^{-\frac{1}{2}} = a^{\frac{1}{2}} = a^b \quad \Rightarrow b = \frac{1}{2} \\ \Rightarrow ab & = \frac{a}{2} = a^{\frac{1}{2}} \quad \Rightarrow a^{\frac{1}{2}} = 2 \quad \Rightarrow a = 4 \\ \Rightarrow b^{-a} & = \left(\frac{1}{2} \right)^{-4} = \boxed{16} \end{aligned}

Everett Thiele
Mar 18, 2018

There's an easy way using log. Taking log of both equations and simplifying by log rules gives a system of equations that you can solve by adding the two rows.

log(a) + log(b) = b log(a)

log(a) - log(b) = 3b log(a)

Adding the rows gives

2 log(a) = 4b log(a)

Because a > 1, log(a)≠0, so you can divide both sides by 2 log(a), giving

1= 2b

b= 1/2

Now it is trivial to get get a a by substitution.

Adrian Peasey
Jul 9, 2015

I did it a longer way using logs.

By taking the log of the first equation we get log ( a b ) = log ( a b ) log ( a ) + log ( b ) = b log ( a ) log ( a ) = log ( b ) b 1 \log\left(ab\right)=\log\left(a^b\right)\Rightarrow \log\left(a\right)+\log\left(b\right)=b\log\left(a\right)\Rightarrow \log\left(a\right)=\frac{\log\left(b\right)}{b-1}

Since a > 1 a>1 the second equation proves b 1 b\neq 1 , meaning this division is allowed.

Taking the log of the second equation we get l o g ( a b ) = log ( a 3 b ) log ( a ) log ( b ) = 3 b log ( a ) log\left(\frac{a}{b}\right)=\log\left(a^{3b}\right)\Rightarrow \log\left(a\right)-\log\left(b\right)=3b\log\left(a\right)

Substituting in log ( a ) = log ( b ) b 1 \log\left(a\right)=\frac{\log\left(b\right)}{b-1} we get log ( b ) b 1 log ( b ) = 3 b log ( b ) b 1 \frac{\log\left(b\right)}{b-1}-\log\left(b\right)=3b\frac{\log\left(b\right)}{b-1}

b 1 log ( b ) 0 1 b 1 1 = 3 b b 1 1 b + 1 = 3 b 4 b = 2 b = 1 2 b\neq 1 \therefore \log\left(b\right)\neq0\therefore \frac{1}{b-1}-1=\frac{3b}{b-1}\Rightarrow 1-b+1=3b\Rightarrow 4b=2\Rightarrow b=\frac{1}{2}

This now gives log ( a ) = log ( 1 2 ) 1 2 1 = 2 log ( 1 2 ) = log ( 4 ) a = 4 \log\left(a\right)=\frac{\log\left(\frac{1}{2}\right)}{\frac{1}{2}-1}=-2\log\left(\frac{1}{2}\right)=\log\left(4\right)\Rightarrow a=4

So b a = ( 1 2 ) 4 = 2 4 = 16 b^{-a}=\left(\frac{1}{2}\right)^{-4}=2^4=\boxed{16}

me too, but I did it this way:

as we have:

a b = a b ab = a^b

we can say

b = log a a b b = \log_a ab

the same way we have:

a b = a 3 b 3 b = log a a b \frac {a} {b} = a^{3b} \Rightarrow 3b = \log_a \frac {a} {b}

Using logarithmic rules we have:

log a a b = log a a + log a b = 1 + log a b \log_a ab = \log_a a + \log_a b = 1 + \log_a b

log a a b = log a a log a b = 1 log a b \log_a \frac {a} {b} = \log_a a - \log_a b = 1 - \log_a b

So:

b + 3 b = ( 1 + log a b ) + ( 1 log a b ) = 2 b = 1 2 b + 3b = (1 + \log_a b) + (1 - \log_a b) = 2 \Rightarrow b = \frac {1} {2}

and then we can easily find a:

b = 1 + log a b 1 2 = 1 + log a 1 2 log a 1 2 = 1 2 b = 1 + \log_a b \Rightarrow \frac {1} {2} = 1 + \log_a \frac {1} {2} \Rightarrow \log_a \frac {1} {2} = -\frac {1} {2}

a 1 2 = 1 2 1 a = 1 2 a = 4 a^{-\frac {1} {2}} = \frac {1} {2} \Rightarrow \frac {1} {\sqrt{a}} = \frac {1} {2} \Rightarrow a = 4

Giorgio de Fornasari - 5 years, 9 months ago
Amed Lolo
Jul 11, 2016

a.b=a^b ,, take( ln) for 2 terms ln(a.b)=ln(a^b) so ln(a)+ln(b)=b.ln(a),,,,,,eq#1 a÷b=a^3.b take ln so ln(a/b)=ln(a^3.b) so. ln(a)-ln(b)=3.b.ln(a) eq #2 ,,,,,eq#1+eq#2 we get 2.ln(a)=4b.ln(a) so b=.5 sub in a.b=a^b a/2=a^.5 so. √a=2 ,,,,a=4. b^-a=.5^-4=16########

Zack Yeung
Jul 9, 2015

first equation let it be ab=a^b........second equation let it be a/b=a^(3b)......manipulate second equation...it becomes a^(3b).b=a..........divide equation one and the manipulateD equation two......after cancelling you will get a^(1-3b)= a^(b-1).....compare power only you get 1-3b=b-1.....then you get b = 1/2........sub b=1/2 back into equation one you get 1/2a=a^(1/2).....square both sides you get a^2-4a=0.........factorise a you get a(a-4)=0....since a>1, a=4........now just put according to the question wanted you get 16

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...